PORTARIA PRR4 Nº 73, DE 7 DE OUTUBRO DE 2004 - Maria Hilda Marsiaj Pinto (BSMPF, Brasília, DF, p. 33-34, 1. quinzena out. 2004., 2004)
Designa os servidores para exercerem a função de Pregoeiros desta Procuradoria Regional.